Investigating the Wear and Hardness of Aluminium LM25 Alloy Reinforced With Nano Al2O3 and Nano TiB2. (2019) - Shanmugaselvam, P.; Sivaraj, S.; Subash, P.
Abstract: The present paper deals with the study of hardness and wear characteristics of Al2 O3 (Nano size) and TiB2 (Nano size) reinforced aluminum LM25 Metal Matrix Composites (MMC). Matrix alloy with 1, 1.5 and 2, 5% of Al2 O3 and TiB2 were made using stir casting technique. A pin on disc wear testing machine was used to find out the wear rate in which E24 steel disc under dry condition and Brinell hardness testing machine was used to find the hardness of the both material made by stir casting. This work mainly emphasis on the comparison of hardness and wear property of the casted material. The wear properties compared in both load and unload conditions. Wear resistance and hardness of the material will be increased when adding the Al2 O3 and TiB2 . The results shown properties of stir casting material having composition 2.5% Al2 O3 + 2.5% TiB2 + 95%LM25 is good compared to the other composition. Because of good dispersion of Nano powders.